A SIMPLE WAY TO LEARN NEW ENGLISH WORDS - Mamadaliyeva Fotima Zokirjon qizi; Boymurodova Feruza Ziyot qizi (Ustozlar uchun, 2025)
Vocabulary learning is an essential aspect of second language acquisition. This article presents a classroom-tested strategy—The Table Method—which helps English learners effectively memorize and recall new words. Unlike passive memorization, this method combines repetition, active recall, and personal organization to strengthen vocabulary retention. Drawing on language learning theories and cognitive psychology, the article also explains how this method aligns with multisensory learning styles. The approach has proven effective among students, increasing both their confidence and vocabulary use in speaking and writing. Practical steps and teaching tips are included, making it suitable for both educators and independent learners.